On the structure of open equivariant topological conformal field theories - Fernàndez-València, Ramsès (Mathematica Scandinavica, 2021)
A classification of open equivariant topological conformal field theories in terms of Calabi-Yau $A_∞ $-categories endowed with a group action is presented.